Incidence, risk factors and outcome of nosocomial pneumonia in patients with central nervous system infections - Gajović Olgica; Todorović Zoran; Mijailović Željko; Čanović Predrag; Nešić Ljiljana; Đorđević Zorana; Stanojević Marijana; Lazić Zorica (Srpski Arhiv za Celokupno Lekarstvo, 2011)
Introduction. Pneumonia is the most frequent nosocomial infection in intensive care units. The reported frequency varies with definition, the type of hospital or intensive care units and the population of patients. The incidence ranges from 6.8-27%. Objective. The objective of this study was to determine the frequency, risk factors and mortality of nosocomial pneumonia in intensive care patients. Methods. We analyzed retrospectively and prospectively the collected data of 180 patients with central nervous system infections who needed to stay in the intensive care unit for more than 48 hours. This study was conducted from 2003 to 2009 at the Clinical Centre of Kragujevac. Results. During the study period, 54 (30%) patients developed nosocomial pneumonia. The time to develop pneumonia was 10±6 days. We found that the following risk factors for the development of nosocomial pneumonia were statistically significant: age, Glasgow Coma Scale (GCS) score <9, mechanical ventilation, duration of mechanical ventilation, tracheostomy, presence of nasogastric tube and enteral feeding. The most commonly isolated pathogens were Klebsiella-Enterobacter spp. (33.3%), Pseudomonas aeruginosa (24.1%), Acinetobacter spp. (16.6%) and Staphylococcus aureus (25.9%). Conclusion. Nosocomial pneumonia is the major cause of morbidity and mortality of patients with central nervous system infections. Patients on mechanical ventilation are particularly at a high risk. The mortality rate of patients with nosocomial pneumonia was 54.4% and it was five times higher than in patients without pneumonia.